A review and analysis of localization techniques in underwater wireless sensor networks - Seema Rani; Anju; Anupma Sangwan; Krishna Kumar; Kashif Nisar; Tariq Rahim Soomro; Ag. Asri Ag. Ibrahim; Manoj Gupta; Laxmi Chand; Sadiq Ali Khan (Tech Science Press, 2023)
In recent years, there has been a rapid growth in Underwater Wireless Sensor Networks (UWSNs). The focus of research in this area is now on solving the problems associated with large-scale UWSN. One of the major issues in such a network is the localization of underwater nodes. Localization is required for tracking objects and detecting the target. It is also considered tagging of data where sensed contents are not found of any use without localization. This is useless for application until the position of sensed content is confirmed. This article’s major goal is to review and analyze underwater node localization to solve the localization issues in UWSN. The present paper describes various existing localization schemes and broadly categorizes these schemes as Centralized and Distributed localization schemes underwater. Also, a detailed subdivision of these localization schemes is given. Further, these localization schemes are compared from different perspectives. The detailed analysis of these schemes in terms of certain performance metrics has been discussed in this paper. At the end, the paper addresses several future directions for potential research in improving localization problems of UWSN.